2019
DOI: 10.4088/pcc.18m02350
|View full text |Cite
|
Sign up to set email alerts
|

US Veterans Who Do and Do Not Utilize Veterans Affairs Health Care Services

Abstract: Objective. To examine sociodemographic and military characteristics of U.S. veterans who do and do not utilize Veterans Affairs (VA) healthcare services as their primary source of healthcare, and examine the relationship between VA utilization and medical and psychosocial characteristics. Methods. Participants were a nationally representative sample of 3,152 military veterans (89.8% male, 83.5% Caucasian, 6.0%, Mage = 62.0, SD = 13.1) who completed a survey assessing healthcare utilization, sociodemographic,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(38 citation statements)
references
References 28 publications
1
36
1
Order By: Relevance
“…Rates of PTSD are known to be higher in veterans than in the general US population. Furthermore, among veterans, the rates of PTSD are higher in those receiving VA care than those who do not [ 46 ]. Veterans who receive care in the VA are also known to have lower education and income than veterans receiving care outside of the VA.…”
Section: Discussionmentioning
confidence: 99%
“…Rates of PTSD are known to be higher in veterans than in the general US population. Furthermore, among veterans, the rates of PTSD are higher in those receiving VA care than those who do not [ 46 ]. Veterans who receive care in the VA are also known to have lower education and income than veterans receiving care outside of the VA.…”
Section: Discussionmentioning
confidence: 99%
“…For example, previous research showed that more than 60% of Medicare eligible older veterans with diabetes received at least some care from non-VHA providers [ 22 ]. The veterans who participated in this study included a relatively large portion of African Americans (48%) as compared to both the overall veteran population who utilize VHA care (about 15%) [ 23 ] and the general Houston population (20%) [ 24 ]. Given the disparities in access to private sector health care faced by people of color, this could have impacted their ability or choice to utilize VHA vs. non-VHA care [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, we examined the overall sample. Then, we stratified by age groups based on prior research that veterans younger than 35 and over 65 are, on average, most likely to use VHA compared to other age groups, 32 which supported three groups: ≤34, 35–64, and ≥65. We also stratified by sex because prior literature illustrates differences in VHA utilization between male and female veterans 33,34 .…”
Section: Methodsmentioning
confidence: 99%